Guarantee of the right to health of patients with HIV and HCV coinfection. The Colombian case - García Cantillo, Karina Margarita; Bravo Villa, María Luisa; Gutiérrez Casalins, Elaine (UNIVERSITAS. Revista de Filosofía, Derecho y Política, 2022)
This paper examines the measures adopted by the Colombian government to meet the needs of the population diagnosed with coinfection of human immunodeficiency virus (HIV) and hepatitis C (HCV), including persons deprived of liberty. To verify such actions, this paper reviewed the guides prepared by the Ministry of Health and the High-Cost Account, in which these diseases have been studied, as well as the legal tools to access to the treatment. The findings indicate that although the Health System in Colombia is not excellent, the truth is the last governments introduced a prevention policy of these illness, besides, appropriated more financial resources that allow an adequate satisfaction of the health needs of this vulnerable group.